Long-term outcomes of epoprostenol therapy in sarcoid associated pulmonary hypertensio - Abston, Eric; Moll, Matthew; Hon, Stephanie; Govender, Praveen; Berman, Jeffrey; Farber, Harrison (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Sarcoidosis-Associated Pulmonary Hypertension (SAPH) is a common finding in patients with chronic sarcoidosis and is associated with increased mortality. The optimal treatment for SAPH is not known; however, therapies approved for Group 1 pulmonary hypertension have improved hemodynamics and functional status. Prostanoids, including epoprostenol, have been therapeutic in short-term studies of SAPH, but long-term efficacy is unknown. In this study, we evaluated the long-term effect of epoprostenol therapy in 12 patients with SAPH. Hemodynamic assessment after an average of 4.1 years of epoprostenol therapy demonstrated significant improvement in mean pulmonary arterial pressure, pulmonary vascular resistance, and cardiac output; furthermore, patients demonstrated improved NYHA functional class. To evaluate further the long-term effect of epoprostenol, we compared survival of SAPH patients to a cohort of hemodynamically matched patients from the same center treated with epoprostenol for Idiopathic Pulmonary Arterial Hypertension (IPAH). Interestingly, there was no difference in survival, despite the additional systemic disease burden of the SAPH subjects. Subgroup analysis by Scadding stage demonstrated that Scadding stages 1-3 had improved survival compared to Scadding stage 4. These observations suggest that epoprostenol is an effective long-term therapy for patients with SAPH; it improves hemodynamics, functional class, and provides survival similar to that seen in a hemodynamically-matched cohort of IPAH patients. Furthermore, we identify a subgroup of SAPH patients (nonfibrotic lung disease Scadding 1-3) who may derive significant benefit from prostanoid therapy.